Radiation-Induced Oral Mucositis in Head and Neck Cancer Patients. Five Years Literature Review - Gkantaifi, Areti; Vardas, Emmanouil; Alongi, Filippo; Tsoukalas, Nikolaos; Saraireh, Haytham H.; Charalampakis, Nikolaos; Lövey, Jozsef; Hajiioannou, Jiannis; Kyrodimos, Efthymios; Tsanadis, Konstantinos; Mauri, Davide; Christopoulos, Christos; et al. (Reviews on Recent Clinical Trials, 2021)
Backround: Radiation-induced oral mucositis consists of a series of relatively frequent side effects after head and neck cancer radiotherapy and has an adverse impact on both regular treatment process and the quality of life of patients. Objective: The purpose of the present review is to optimize the current management of radiation-induced oral mucositis in head and neck cancer patients. Methods: PubMed database research was performed on articles published since 2015 that demonstrated efficacy in the management of radiation-induced oral mucositis in head and neck cancer patients. The study selection included observational, prospective, comparative, randomized, double- blind, placebo-controlled or uncontrolled, and retrospective studies, as well as systematic reviews and metanalyses. Results: From the 931 citations obtained from the search, only 94 articles met the inclusion criteria, including mucosal protectants, anti-inflammatory agents, growth factors, and various miscellaneous and natural agents. Several methods, including both pharmacological and natural agents, have been proposed for the management of oral mucositis. In addition to the already known interventions with strong evidence, according to the Multinational Association of Supportive Care in Cancer and he International Society of Oral Oncology guidelines, further agents have been used. However, a great number of them lack clear evidence, which surely requires the design of more controlled clinical trials for a better assessment of the ideal methods. Conclusion: The management of oral mucositis constitutes an active area of research. In light of these results, it is aimed to illustrate those treatment strategies that are most effective regarding the treatment approach of oral mucositis.
Keywords: Oral mucositis